Students’ Perception Toward Teaching Reading - Nurwanti (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
The objective of this research is to find out the students’ perception toward teaching reading, it uses a qualitative research with descriptive approach. The subject of the research were 13 the second semester students of English Education Department at Lakidende Unaaha University by using purposive sampling technique. The data collected by distributing questionnaire that designed by Likert scale, and data of it were analyzed by using Formula of Suherman & Sukjaya (1991) (Malik, 2018, p 88). The result of this research shows that most of students give the positive response. Students mostly chose the alternative response “Agree” in answering the questionnaire given. The alternative response “Strongly Agree” occupies the second position most chosen by students, and the third position is the alternative response “Not Sure”. Based on the findings, it can be concluded that students have a positive perception to their lecturer’s way of teaching reading subject. In addition, the lecturer can motivate and help students to learn material, especially those related to everyday life, and also the lecturer has the detailed explanation that can make easier for students to understand the subject properly.